KONSTRUKSI PEREMPUAN TERHADAP IMPLEMENTASI RANCANGAN UNDANGUNDANG PENGHAPUSAN KEKERASAN SEKSUAL - Trianggono, Yudha Guruh (Paradigma, 2021)
Humans are created in pairs between men and women, often in society, men and women are differentiated based on gender or what we are more commonly known as gender bologically. The background of sexual violence, which starts with the perspective of each person differentiating on the basis of gender, causes frequent sexual harassment in society. Sexual violence in society is increasing over time, so there is a need for a solution to overcome this problem, one of which is a rule that enforces every case of sexual violence so that it does not happen again in society. The regulation in question is the Draft Law on the Elimination of Sexual Violence. The purpose of this study is to determine the government's efforts in dealing with sexual harassment in society, to identify other solutions in overcoming sexual violence, to analyze women's construction of the PKS Bill in addressing the problem of sexual violence. This study uses a qualitative method with a perspective, the researcher tries to describe and interpret the conditions or circumstances in society. The results of this study are divided into three discussions, namely in the political, social and legal fields. In the political field, the opportunity to enter the political sphere is increasingly open, women can nominate regional heads, legislative members or other positions. In the social sector, it is hoped that this regulation can reduce the number of cases of sexual violence in the public sphere. This rule guarantees women who often have activities outside the home so that they do not get harassed by men. By providing a deterrent effect for perpetrators who often sexually harass women in public places such as buses, terminals, markets, malls, etc. In the field of law, it is hoped that it can suppress sexual violence against women. Not only law, but enforcement must also be monitored so that it is in accordance with what is expected, do not let the law only apply to the lower class society, while cases that befall the upper class are often negligent and are not investigated, so that people's perceptions of the law will increase and society will comply with any rules made by the state. Keywords: Gender, Law, Women's Construction, Sexual Violence.